2018
DOI: 10.5210/ojphi.v10i3.9544
|View full text |Cite
|
Sign up to set email alerts
|

Websites as a tool for public health education: determining the trustworthiness of health websites on Ebola disease

Abstract: ObjectivesHealth service providers use internet as a tool for the spreading of health information and people often go on the web to acquire information about a disease. A wide range of information with varying qualities and by authors with varying degrees of credibility has thus become accessible by the public. Most people believe that the health information available on the internet is reliable. This issue reveals the need for having a critical view of the health information available online that is directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
3
18
0
1
Order By: Relevance
“…The privacy policy is among seven core issues of website usability design and is of particular importance in creating effective websites [ 60 ]. Most websites assessed in this study had specified their privacy policy which is in line with the researches that have been carried out on other health topics [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 92%
“…The privacy policy is among seven core issues of website usability design and is of particular importance in creating effective websites [ 60 ]. Most websites assessed in this study had specified their privacy policy which is in line with the researches that have been carried out on other health topics [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the results of the present study were consistent with the results of similar studies conducted on the evaluation of non-Persian language websites in other health topics. Their findings showed unreliability and poor quality of health websites [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…HONcode is the oldest and most-used ethical and trustworthiness code for medical and health-related information available on the Internet [64]. It is reliable and has been used in multiple studies to assess the credibility of health websites [11,12,[14][15][16][65][66][67]. Therefore, we used the HONcode toolbar to identify certified websites containing information on COVID-19.…”
Section: Credibility Evaluation Toolmentioning
confidence: 99%
“…On March 13, 2020, Google Trends reported that the term "coronavirus" was searched five million times (supplemental appendix), underlining the importance of the Internet as a source for health information. However, multiple studies demonstrate that health websites may not be credible and may contain inaccurate or misleading information [11][12][13][14][15][16]. Therefore, the information found on health websites could increase uncertainty and anxiety and, thereby, serve to harm people's health [17][18][19].…”
Section: Introductionmentioning
confidence: 99%